SISTEM PENJAMINAN MUTU PERGURUAN TINGGI MELALUI EVALUASI MUTU INTERNAL (EMI) UNIVERSITAS BATANGHARI JAMBI - Sri Marmoah (Universitas Batanghari Jambi, 2014)
In preparation to meet the external evaluation conducted by BAN-PT, it is necessary to evaluate the internal quality (EMI) at the University of Batang (Unbari). Evaluation of internal quality (EMI) is a systemic activity of higher education quality assurance in higher education by universities (internally driven), to oversee the implementation of higher education by the universities themselves on an ongoing basis (continuous improvement). Evaluation of internal quality (EMI) aims to help universities and government development programs towards meeting set SNPT, and avoid the gap between the results of the internal evaluation with external evaluation. With EMI conducted is expected to provide benefit in facilitating the mapping quality higher education, facilitate resource sharing and partnership between PT and with other institutions (government, industry, and society), as well as facilitate feedback mechanism that is coaching and development by the government and as an ingredient reference for stakeholders involved in mapping quality higher education. EMI planning process begins with the first step to form the EMI team to conduct outreach programs in the Faculty of Teacher Training and Education (LPTK) and other Faculty (Non-LPTK) in Unbari environment. Then the next process and how to fill the training conducted EMI involving all faculties in Unbari and proceed with filling EMI. The evaluation was conducted after all the programs from starting up with the socialization process of filling EMI. Internal Quality Evaluation Results (EMI) in both the EMI and EMI LPTK Non-LPTK of 10 standards that have been set from the overall average of 48,20 this suggests that the overall aspect of the necessary minor repairs and improvements to all aspects of continuous, mainly on standard research, community service standards, and standards for the cooperation of the three standards below the average figure of 40. From the results of the recommended first EMI, EMI results LPTKs and Non-LPTK need to be followed by monitoring and evaluation (M & E) is constantly. Second, EMI must be implemented consistently in the Unbari. Third, The Foundation and all the elements of leadership needs to give particular support infrastructure and financing, and the fourth needs to be increased empowerment of human resources, especially lecturers in order to better understand and participate in the implementation of quality assurance both internal and external.Keywords: Quality Assurance System, Internal Quality Evaluation, University of Batanghari